The complete mitochondrial genome of sand anemone, Paracondylactis hertwigi (Wassilieff, 1908) - Seung-Joon Lee; Sang-Hwa Lee; Hyo-Jin Yu; In-Young Cho; Sung-Jin Hwang (Mitochondrial DNA. Part B. Resources, 2025)
This study reports the complete mitochondrial genome of Paracondylactis hertwigi (Actiniidae) for the first time. The mitogenome is 19,880 bp in length and contains 17 annotated genes, including 13 protein-coding genes, one nonconventional mitochondrial protein gene (ORF), two ribosomal RNA genes, and two transfer RNA genes. The gene content, order, and genome length are consistent with those of other sea anemones. Notably, the COX1 and ND5 genes each consist of two exons separated by an intron, with ND1 and ND3 genes encoded within the ND5 intron, confirming the conservation of this unique mitochondrial genomic structure in Actiniaria. Phylogenetic analysis revealed that Paracondylactis is paraphyletic, with P. sinensis clustering outside the genus alongside species of the family Phymanthidae. These results align with previous findings of paraphyly within Actiniidae and support the hypothesis that the family is polyphyletic within the superfamily Actinioidea, reflecting limitations in morphology-based classifications. Further studies integrating morphological and molecular phylogenetic approaches are needed to clarify the taxonomic relationships within the genus Paracondylactis. Additionally, the mitogenomic data of P. hertwigi may serve as a valuable resource for the genetic management and conservation of tidal flat organisms in Korea, which are increasingly threatened by coastal development and climate change.